Керамика «минаи» из Азака - Кравченко, С.А. (Степи Европы в эпоху средневековья, 2012)
The paper presents samples of the “minai” kashin pottery with over-glaze polychromatic painting and gilding over white opaque glaze, which were found during excavations of the Golden Horde Azak (13lh-14lh centuries). All of the 35 fragments from 21 vessels have been described. On the basis of the findings, the author has analysed the morphology of the vessels, the quality and composition of the moulding paste, the colour gamma and the stylistics of decoration, the chronology, and the quantitative data of “minai” pottery from Azov.